Exploring Ototoxicity Associated with Capmatinib: Insights from a Real-World Data Analysis of the FDA Adverse Event Reporting System (FAERS) Database - Lin Y; Xu S; Deng M; Cao Y; Ding J; Lin T (Clinical Epidemiology)
Yuhao Lin,1,* Siqi Xu,1,* Muling Deng,1 Yongli Cao,2 Jianming Ding,1 Tingting Lin3 1Department of Radiation Oncology, Clinical Oncology School of Fujian Medical University, Fujian Cancer Hospital, Fuzhou, Fujian, People’s Republic of China; 2Department of Nursing, the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 3Department of Operation, Clinical Oncology School of Fujian Medical University, Fujian Cancer Hospital, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tingting Lin, Department of Operation, Clinical Oncology School of Fujian Medical University, Fujian Cancer Hospital, Fuzhou, Fujian, 350014, People’s Republic of China, Email MDTINGting1@163.com Jianming Ding, Department of Radiation Oncology, Clinical Oncology School of Fujian Medical University, Fujian Cancer Hospital, Fuzhou, Fujian, 350014, People’s Republic of China, Email djm_1991@fjmu.edu.cnBackground: Capmatinib was approved by the US Food and Drug Administration (FDA) in 2020 for the treatment of non-small cell lung cancer with MET exon 14 mutation (METex14). Real-world studies on the safety of Capmatinib are still lacking. The aim of this study was to explore the significant adverse drug reactions (ADRs) associated with Capmatinib through the FDA Adverse Event Reporting System (FAERS) database.Methods: We employed the reported odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and the Empirical Bayes Geometric Mean (EBGM) as primary algorithms for the disproportionality analysis. Adverse events (AEs) were classified as adverse drug reactions (ADRs) solely upon fulfillment of criteria across all four algorithms.Results: In our study, there were 1767 cases explicitly attributed to Capmatinib. A total of 38 ADRs in preferred terms (PTs) level in 14 system-organ categories (SOCs) were identified after filtering. Notably, unexpected SOC “Ear and labyrinth disorders” and PTs “hypoacusis” and “deafness” were identified, without being specified in the drug label.Conclusion: Our study identified unexpected ADRs associated with Capmatinib, with a focus on ototoxicity-related events, underscoring the need for enhanced clinical monitoring and further investigation into the underlying mechanisms.Keywords: Capmatinib, adverse drug reactions, data mining, pharmacovigilance, targeted drug